1997
DOI: 10.1063/1.119383
|View full text |Cite
|
Sign up to set email alerts
|

Activation field of ferroelectric (Pb,La)(Zr,Ti)O3 thin film capacitors

Abstract: Articles you may be interested inPolarization fatigue in Pb Zr 0.45 Ti 0.55 O 3 -based capacitors studied from high resolution synchrotron x-ray diffraction J. Appl. Phys. 97, 064108 (2005); 10.1063/1.1870098 Effect of oxygen stoichiometry on the ferroelectric property of epitaxial all-oxide La 0.7 Sr 0.3 MnO 3 /Pb(Zr 0.52 Ti 0.48 )O 3 /La 0.7 Sr 0.3 MnO 3 thin-film capacitors High resolution study of domain nucleation and growth during polarization switching in Pb(Zr,Ti)O 3 ferroelectric thin film capacitors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 10 publications
(3 reference statements)
1
17
0
Order By: Relevance
“…It has been widely reported that an increase in the frequency produces a continuous increase in the coercive field. This behavior has been observed in single crystals, 26,27 bulk ceramics 28,29 and thin films 30 . However, recently, some experimental results showed that the frequency dependence of the coercive field is strongly dictated by the kind of defect introduced into the crystalline lattice, not necessarily increasing with the increase of the frequency.…”
Section: Introductionsupporting
confidence: 54%
“…It has been widely reported that an increase in the frequency produces a continuous increase in the coercive field. This behavior has been observed in single crystals, 26,27 bulk ceramics 28,29 and thin films 30 . However, recently, some experimental results showed that the frequency dependence of the coercive field is strongly dictated by the kind of defect introduced into the crystalline lattice, not necessarily increasing with the increase of the frequency.…”
Section: Introductionsupporting
confidence: 54%
“…29 Interaction of domain walls with point defects may also result in a high activation field. 30 Thus, the first decrease of activation fields ͑x Ͻ 0.04͒ is attributed to the decrease of oxygen vacancy caused by W doping. When x Ͼ 0.04, the increase of activation field is mainly attributed to the reduction of switchable polarization caused by Bi vacancy induced deterioration of crystal cell integrality.…”
Section: Switching Propertiesmentioning
confidence: 98%
“…As such, ferroelectric characteristics are naturally frequency-dependent. The study of frequency dependence in ferroelectrics has a long history that could be dated back to the experimental investigations of Wieder [1] and Pulvari and Kuebler [2] for single crystals, Song et al [3] for thin films, and Viehland and Chen [4], Lente et al [5], and Eiras and Lente [6] for bulks, among others. A common feature of the reported data is that the coercive field tends to increase with loading frequency.…”
Section: Introductionmentioning
confidence: 99%